Identification of CXCR4 as a potential preventive gene in clear cell renal cell carcinoma from machine learning and immune analysis - Fengming Hu; Xiao Wang; Runsheng Wu; Sihong Liu; Hongli Liu; Ranran Dai (Scientific Reports)
Abstract Clear cell renal cell carcinoma (ccRCC) represents a prevalent malignant kidney tumor characterized by high metastatic potential and recurrence rates. Investigations into the molecular mechanisms and therapeutic targets of ccRCC have provided novel directions for early diagnosis and targeted therapy. The CXCR4 gene plays a pivotal role in tumor progression and metastasis. In this study, this study first conducted differential analysis and WGCNA analysis on the dataset, and performed GO and KEGG analysis on the differentially expressed genes, revealing key biological processes and signaling pathways, particularly in cell adhesion and immune regulation. Based on WGCNA and cross genes of differentially expressed genes, 50 central genes were identified through PPI analysis. LASSO, SVM-RFE, and RF algorithms are used to identify the key gene CXCR4 associated with ccRCC. Survival analysis revealed that high CXCR4 expression correlates with poor patient prognosis. Immune analysis highlighted differences in immune cell distribution across ccRCC subtypes, emphasizing the importance of gene-immune interactions in disease pathogenesis. Finally, validation was conducted in vitro using techniques such as PCR and Western blot. Our findings position CXCR4 as a potential preventive gene, offering new theoretical insights for early diagnosis and targeted treatment of ccRCC.